Effects of land reclamation activities on fish catch among fishermen at Merambong Shoal, Johor - Kamarulzaman, Nitty Hirawaty; Jumain, Nora Azura (HH Publisher, 2023)
The fisheries community is a community that is highly dependent on the fisheries sector, and they usually live near the coastal area.  However, land reclamation activities are conducted in the coastal area for development and urbanization due to the increasing population. Consequently, the land reclamation activities degraded the habitat of the fish and caused a decrease in their productivity. This study investigated the effects of land reclamation activities on fish catch among fishermen. Using convenience sampling, 79 fishermen in the Merambong Shoal were selected, and a structured questionnaire was constructed to get responses from these fishermen. Descriptive analysis, factor analysis, and multiple regression analysis were used to analyze the data. The study revealed that the number of trips, duration of fishermen to catch fish, distance of fishing ground from the coast, number of crew, and government incentives were the factors that affected the fish catch. These factors have significant relationships with the quantity of fish catch, which directly impacts income and, at the same time, affects livelihoods. The role of the government in increasing the monetary incentives and subsidies to improve the fishermen's fishing operations was highly recommended.